Graphene Oxide Modified Electrodes for Dopamine Sensing. (16th April 2017) - Khan, M. Z. H.
Abstract : Dopamine (DA) is one of the most important catecholamine neurotransmitters that plays an important role in the central nervous, renal, hormonal, and cardiovascular systems. Since its discovery, tremendous effort has been made and various techniques have been developed for the DA detection. Recently, graphene-based materials have attracted a tremendous amount of attention due to their high sensitivity and rapid response towards effective detection of DA. This review focuses on current advances of graphene-based materials for DA detection based on recent articles published in the last five years.